Can psychological variables be related to the level of the immunological parameters essential in the course of pregnancy? - Rolińska, Agnieszka; Darmochwał-Kolarz, Dorota; Pietrzak, Aldona; Makara-Studzińska, Marta (Polish Journal of Public Health, 2010)
Aim. The presented investigation attempts to describe the relation between the number of leukocytes in the peripheral blood of pregnant women and the following psychological variables: the feeling of coherence, anxiety as a state and as a trait, and styles of coping with stress. Material and methods. The study group consisted of 64 pregnant women. The following tests were used in describing the psychological variables: State-Trait Anxiety Inventory (STAI), Coping Inventory for Stressful Situations (CISS), Sense of Coherence Questionnaire (SOC-29). The hematological meter was used to describe the morphology of blood. Results. A scrupulous analysis suggests the existence of significant correlation between the quantity of leukocytes and the avoiding style of coping with stress. This method was least often used by the women who had the smallest average number of leukocytes. No high correlation between the number of leukocytes and the sense of coherence and/or anxiety has been observed.